Patricians and Popolani The Social Foundations of the Venetian Renaissance State - Romano, Dennis, 1951-; Project Muse.; Project Muse. (2019)
Community and conflict in early Renaissance : Family structure and marriage ties : The world of work : guild structure and artisan networks : The parochial clergy and communities of the sacred.
One. Community and conflict in early Renaissance Venice -- Two. Urban form and social stratification: The Civitas Venetiarum -- The evolution of the early Renaissance city -- Patricians, popolo grande, and popolo minuto -- Three. Family structure and marriage ties -- The patrician family -- The popolo grande family -- The popolo minuto family -- Four. The world of work: guild structure and artisan networks -- Production techniques and guild structure -- The social world of Venetian artisans -- Five. The parochial clergy and communities of the sacred -- The parish clergy as social intermediaries -- Communities of the sacred -- The parish clergy as social intermediaries -- Communities of the sacred -- Six. Vicinanza and Amicizia: neighborhoods and patronage in early Renaissance Venice -- Male patronage: the development of state-centered ties -- Neighbors and friends: female patronage -- Seven. From community to hierarchy: the transformation of Venetian social ties -- Venetian society in the early Renaissance -- From community to hierarchy.
Originally published as Johns Hopkins Press,1987
Includes bibliographical references (pages 199-213) and index.
Description based on print version record.
Keywords: Venice (Italy) -- History -- 697-1508.; Venice (Italy); Renaissance -- Italy -- Venice; Community organization -- Italy -- Venice -- History; Social structure -- Italy -- Venice -- History; Social classes -- Italy -- Venice -- History; Electronic books; Electronic books